A Ringed Enigma: The Clinical Spectrum of Granuloma Annulare. Issue 2 (March 2020) - Zahirsha, Zisansha; Lake, Eden
Abstract : ABSTRACT: Granuloma annulare is a poorly understood disease typically presenting as localized, nonscaly, annular plaques on the dorsal extremities. Clinical variants, such as generalized, patch, perforating, and subcutaneous types, exist. Therefore, granuloma annulare has a broad range of clinical morphologies and presentations. Knowledge of the clinical features, prognosis, and treatment options of the disease is critical for providers to appropriately diagnose and manage the condition.